PERAN PENYULUH PERIKANAN DALAM MEMBINA KELOMPOK PENGOLAH DAN PEMASARAN “MEKAR BERSAMA” KELURAHAN MUARA SEMBILANG KECAMATAN SAMBOJA KABUPATEN KUTAI KARTANEGARA - Fitria; H. Helminuddin; Qoriah Saleha (2339-1324, 2020)
The aim to know the role of fishery Extension Worker in guiding “Mekar Bersama” Management and Marketing Group in Muara Sembilang Sub-Village, Samboja Sub-District. Sampling determination used census method which is all population members (“Mekar Bersama” Management and Marketing Group) amounting to 11 people became the research respondents. Score data (highest score is 3 and lowest score is 1) from the questionnaire guided by likert scale was analyzed using interval class formulation. The result of this research is the role of fishery Extension Worker in developing “Mekar Bersama” Management and Marketing Group with the average score of 59.81 at the range of 50.01-63.00 included to the high level. It means that the Extension Worker in Muara Sembilang Sub-Village is able to implement his Extension Worker role as motivator, catalyst, educator organizator, communicator, and advisor